Mobile weather apps or the illusion of certainty. (October 2016) - Zabini, Federica
ABSTRACT: A huge change has occurred in the way people obtain weather information in the last few years and a large percentage of the population now get weather forecasts on their mobile phones. There is currently a wide range of smartphone weather apps available: in 2014, iTunes App Store alone offered 5043 active applications in the weather category. The rapid penetration of new broadcasting technologies strongly affects the way weather forecasts are communicated to, and used by, people. Portability, permanent connectivity and geolocalization allow location‐specific and time‐sensitive weather forecasts to be provided. This paper explores the main features emerging in the 39 most popular weather apps in the United States, United Kingdom and Italy, and focuses on the implications in the communication of uncertainty. The results show that even if the advances in mobile communication technologies could, in principle, improve the effectiveness of weather communication enormously, the expectations created around weather forecasts appear to be inconsistent with current forecasting capabilities, particularly with their inherent uncertainties in space and time, as well as in the nature of the predicted weather events.